Punitive Operations Carried out by Lithuanian Partisans in Alytus County in 1944–1952 - Zagreckas, Rimantas (Genocidas ir rezistencija, 2017)
To compare with guerrilla wars in the 20th century in Europe, participants of Lithuanian partisan movement after the WW II were particularly involved in fighting collaborationism; they were struggling to overcome challenges related to support showed by their fellow citizens to the Soviet authorities. In the majority of cases, the punitive operations were precalculated actions, by which it was sought not to allow the Soviets to entrench deeply their authority in this country; yet, in part, it had been spontaneous responses towards substantial reforming of social relations and world view norms prevailing in Lithuania (especialy in the countryside). New norms had to comply with the bolshevist communist ideology version.In the beginning, fighting collaborationism had not been the most important part of partisan activity, yet, under conditions of increasing involvement of local people in the schemes of repressive structures (first of all, those of NKVD and MGB), the number of counter-punitive operations increased. Especially violent fight of this kind broke out in South Lithuania, first of all, in Dzūkija, as in this region, Dainava and Tauras military districts of partisans were established. Those two military districts were stronger and resisted longer to compare with other ones. It is likely that earlier, the leaders of first military groups of partisans acted spontaneously, they were following their own understanding of ethics. Although a part of them had to have access to the Order of 10th November 1944 of Headquarters of Lithuanian Freedom Army formally functioning across Lithuania. The Order contained information related to citizens behaviour concerning collaborationism. Later, the leaders of partisan military districts drafted legal acts, more or less adapted to war time conditions, regulating partisan fight tactics and methods against collaborations.Statistics collected when preparing this article shows that in 1941 – 1952, in the biggest Dzūkija county, Alytus county, Lithuanian partisans claimed the lives of more than 1 450 people (this number includes victims of clashes with the NKVD and MGB units). About 300 (21 per cent) of them were killed during mass assaults on one or several villages; later these events were named Bartholomew‘s Day Massacre. The majority of the victims were people who contributed more or less to entrenchment of Soviet system in Lithuania, although it is problematic to determine the exact number of such people, because, when investigating concrete cases, frequently, one is not able to reconstruct all circumstances of the event. Those cases when entire families were killed together with underage children are to be considered criminal offences unambiguously – no justification documents have been found concerning such actions in the written legacy of the partisans (several concerete cases demonstrate that partisan leaders considered a person of 14 years of age fully responsible for his / her actions).
Keywords: Lithuania; Soviet occupation; partisans; armed resistance; punitive policy; Alytus district